Konsistensi Identitas Visual: Kajian Visual Branding Media Publikasi Borobudur - Muh Ariffudin Islam (Jurnal Desain Komunikasi Visual Asia, 2019)
ABSTRACT Many entities still do not understand the importance of consistently using graphic elements. In the absence of consistency between media, it will create an "impression" of a gap within a brand, so that the media does not seem to support each other. Borobudur, which is one of the largest tourist assets in Indonesia, certainly has its own charm from domestic and foreign tourists. Along with the development of information technology, the carrying capacity of tourism continues to be improved and developed, one of which is publication media. So much Borobudur publication media, makes it interesting to study. This study aims to determine the constants and variables of design in the media used for the interests of Borobudur branding identity. These objectives will be achieved by a descriptive-analysis path that is based on qualitative methods. The effort that is done is by describing the visual variable to find out the reality of the actual sign. Some examples of publication media used as object of analysis can show the consistency level of publication media used by Borobudur managers. The existence of a visual consistency gap shown in each media can weaken Borobudur's brand identity from the perspective of society. Keywords: branding, design, identity, consistency, visual